No banzeiro do lago: a (in) sustentabilidade do turismo na representação dos barqueiros atingidos pela UHE Estreito em Babaçulândia-TO - Zagallo, Ana Daisy Araújo (Universidade Federal do Tocantins, 2018)
In the bias of the studies on the socio-environmental impacts of hydroelectric dams in the Amazon region, this research aimed to demonstrate the touristic (un) sustainability of the municipality of Babaçulândia-TO from the boatmen's perspective affected by the Estreito Hydroelectric Power Plant that, when installed in the Tocantins River, extinguished their navigation routes and interrupted the seasonal tourism from which they made their living. Based on the theoretical-analytical assumptions of the theory of the social representations of Serge Moscovici, the representations of the boatmen were taken in this research as indicators of tourism sustainability. Of qualitative nature, the study adopted a multi-method strategy, combining techniques of oral history, unsystematic observation and semi-structured interview. Being a socially constructed knowledge, the boatmen's representations not only express their own impressions on the material and symbolic losses resulting from the hydroelectric enterprise, but also project the ills and the desires of a community that tries to overcome the effects of the transformations due to the dam of the river Tocantins in their lives. In this sense, it was tried to demonstrate how the decharacterization of the place and the riverside way of life interrupted the tourist cycle of the city, provoking its early decline and compromising its sustainability. Thus, considering that touristic unsustainability constitutes a social and environmental liability of the Estreito HPP, the boatmen's social representations became concrete elements, products of a symbolic dimension that reflected a reality capable of qualifying the development of tourism in the post-hydroelectric context.